Inhibition of NF-κB Signaling Pathway by Resveratrol Improves Spinal Cord Injury - Xu, Luyao; Botchway, Benson O. A.; Zhang, Songou; Zhou, Jingying; Liu, Xuehong (Frontiers in Neuroscience, 2018)
Spinal cord injury (SCI) can have a significant impact on an individual’s life. Herein, we discuss how resveratrol improves SCI by inhibiting NF-κB signaling pathway. Evidences show resveratrol suppresses NF-κB signaling pathway to exert its multifarious beneficial effects on various diseases. NF-κB signaling pathway plays a significant role in the pathophysiological mechanisms of SCI including aggrandizement of inflammation, augmentation of damage caused by free radicals and lipid peroxidation as well as facilitation of apoptosis and axonal demyelination. We also discuss mechanisms between resveratrol and NF-κB signaling pathway in the wake of SCI, which can be potential targets for resveratrol to treat SCI.